(untitled) (Applied Biological Research, 2025)
Among natural products the phytochemicals are emerging as an important area of research, wherein lichens have attracted immense attention for their exceptional potency to cure various diseases. To explore the phytochemical and medicinal importance of lichens from India Heterodermia boryi, H. diademata and Lobaria retigera were analysed through gas chromatography-mass spectrometry. Hexane-, chloroform- and methanolic-extracts of each lichen were assessed for antimicrobial and antioxidant properties. The methanolic extracts of lichens showed the presence of 68 phytochemicals like hydroxychalcone, normethadol, pinostilbene, pipemidic acid, acid, iodohiistidine, pyridine, pheophorbide a, chromone, isoorientin, dimethoxyflavone, perchloryl fluoride, sulforaphane and carvacrol. Methanol extracts of all the three species showed highest zone of inhibition ranging from 10.7±0.06 to 26.8±0.06 mm. All the extracts of three species exhibited potent antimicrobial activity against S. typhi followed by K. pneumoriae. Of the three extracts methanol extracts of both H. boryi and H. diademata showed the highest antioxidant activity with 0.899 and 0.62 mg g1 ascorbic acid equivalent, respectively. While hexane and chloroform extracts of H. boryi showed highest radical scavenging activity followed by hexane and chloroform extract of H. diademata and hexane extract of L. retigera.